Recommendations for implementing distributed ledger technology (blockchain) in the public sector of Ukraine based on global experience - Basiuk, Oleksandr (Pressing Problems of Public Administration, 2023)
Integrating new technologies such as distributed ledger technology into government systems is a multifaceted process characterized by numerous potential benefits, associated costs, and risks. Previous and existing pilot implementations of blockchain-based software solutions in the public sector have demonstrated that this technology can have varying impacts depending on contextual factors, including the specific type of chosen government service. Furthermore, within each distinct area of public services, the implementation of e-governance technologies can yield different outcomes for various stakeholders, including government entities, public servants, and citizens.Therefore, this article provides a review and analysis of global experiences with the utilization of distributed ledger technology in various domains of the public sector. To achieve this, several countries with advanced expertise in e-governance and the implementation of distributed ledger technology-based solutions were identified. Drawing from the experiences of these nations and considering the unique features, advantages, maturity level of blockchain technology, and existing solutions based on it, general recommendations were formulated regarding the implementation of distributed ledger technology (blockchain) in Ukraine’s public sector.